Modulating cell adhesion to polybutylene succinate biotextile constructs for tissue engineering applications - Ribeiro, Viviana Pinto (2017)
Textile-based technologies are powerful routes for the production of three-dimensional porous architectures for tissue engineer- ing applications because of their feasibility and possibility for scaling-up. Herein, the use of knitting technology to produce polybutylene succinate fibre-based porous architectures is described. Furthermore, different treatments have been applied to functionalize the surface of the scaffolds developed: sodium hydroxide etching, ultraviolet radiation exposure in an ozone atmosphere and grafting (acrylic acid, vinyl phosphonic acid and vinyl sulphonic acid) after oxygen plasma activation as a way to tailor cell adhesion. A possible effect of the applied treatments on the bulk properties of the textile scaffolds has been considered and thus tensile tests in dry and hydrated states were also carried out. The microscopy results indicated that the surface morphol- ogy and roughness were affected by the applied treatments. The X-ray photoelectron spectroscopy and contact angle measure- ments showed the incorporation of oxygen-containing groups and higher surface free energy as result of the surface treatments applied. The DNA quantification and scanning electron microscopy analysis revealed that these modifications enhanced cell adhesion and altered cell morphology. Generally, sodium hydroxide treatment altered most significantly the surface properties, which in turn resulted in a high number of cells adherent to these surfaces. Based on the results obtained, the proposed surface treatments are appropriate to modify polybutylene succinate knitting scaffolds, influencing cell adhesion and its potential for use in tissue engineering applications.Â